The complete mitochondrial genome of Fruhstorferiola tonkinensis (Orthoptera: Catantopidae). Issue 1 (1st January 2016) - Zhang, Xinmei; Lin, Liliang
Abstract: Fruhstorferiola tonkinensis belongs to the group of Catantopidae, which is the largest group in Acridoidae. The complete mitochondrial genome (mitogenome) of Fruhstorferiola tonkinensis is 15, 637 bp in length, including 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA genes and 1 A + T-rich region. The gene order and arrangement are identical to other Acridoidae species. Most PCGs (except for the ATP6) start with the typical ATN codons, while most stop codons are TAA, TAG. The combined dataset of 13 PCGs and 2 rRNAs from 17 grasshoppers (including 15 Catantopidae species and 2 outgroups) is used to construct phylogenetic tree and analyse phylogenetic relationship of Catantopidae.